DETERMINAN KEPUASAN PENGGUNA AKHIR APLIKASI ERP FREE OPEN SOURCE ADEMPIERE PADA USAHA KECIL MENENGAH: STUDI KASUS PADA UKM BLESSINGS - Dionysia Kowanda; Muhammad Firdaus; Rowland Bismark Fernando Pasaribu (Fakultas Bisnis UKDW, 2016)
In a small-sized to big-sized company, evaluate the information system success is essential, yet notalways been seamless. Successful implementation of a system can be indicated by measuring its usersatisfaction. This study aims to measure Adempiere ERP Open Source end-user satisfaction atBlessings SME’s. This study employs three variables from The Updated DeLone and McLean Information System Success (2003), namely information system quality, information quality, andservice quality, and two variables from Technology Acceptance Model (TAM) as well, namely perceived usefulness and perceived ease of use, and also takes top management support as another consideration. Data were collected by distributing questionnaires to the respondents directly concerned. The findings showed that information quality, perceived usefulness, perceived ease of use, and top management support have significant positive impact to Adempiere ERP Open Source enduser satisfaction, whereas information system quality and service quality have positive impact but not significantly.Keywords: Small-Medium Enterprises, information system quality, information quality, servicequality, perceived usefulness, perceived ease of use, top management support, end usersatisfaction, information system